High-flexibility and high-conductivity electrothermal film, preparation method and application thereof in heating gloves

By using lithium bistrifluoromethanesulfonimide and cobalt phthalocyanine doped polymers and surface-modified graphene/carbon nanotube composite filler in the electric heating film, the problem of insufficient flexibility and conductivity of the electric heating film is solved, and the problem of insufficient flexibility and conductivity of the electric heating film is achieved. High flexibility, high conductivity and self-healing performance are improved, suitable for applications such as heating gloves.

CN119286199AActive Publication Date: 2025-01-10SHENZHEN EIGDAY HEATING LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411498647.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-10
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

The existing electric-heating films have shortcomings in flexibility, self-healing and conductivity, and it is difficult to meet the requirements of high flexibility, high conductivity and self-healing performance at the same time.

Method used

Designed with lithium bistrifluoromethanesulfonimide and cobalt phthalocyanine doped poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid), combined with surface modified graphene/carbon nanotube composite The filler was grown in situ on the surface of carbon nanotubes by CVD method and functionalized in strong acids to enhance the flexibility and conductivity of the film.

Benefits of technology

It significantly improves the flexibility and conductivity of the film, forms a continuous nanofiber network, enhances mechanical and thermoelectric properties, and is suitable for flexible electric heating devices such as heating gloves.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119286199A_ABST
    Figure CN119286199A_ABST
Patent Text Reader

Abstract

The invention relates to the field of electric heating materials, in particular to a high-flexibility and high-conductivity electric heating film, a preparation method and application, and the electric heating film is mainly prepared from the following components in parts by weight: a doped conductive prepolymer, a surface modified graphene / carbon nanotube composite filler, a styrene-ethylene-butylene-styrene block copolymer, N-methyl pyrrolidone and the like. The surface modified graphene / carbon nanotube composite filler is treated by concentrated sulfuric acid and concentrated nitric acid, and the doped conductive prepolymer is prepared from poly (3, 4-ethylenedioxythiophene)-poly (styrenesulfonic acid), lithium bis (trifluoromethanesulfonimide) and the like. The electrothermal film with excellent flexibility, conductivity and heating performance is prepared through reasonable proportioning and a dispersing process, the problems of poor conductivity and insufficient flexibility in the prior art are solved, and the electrothermal film can be widely applied to the fields of flexible electronic devices in heating gloves and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrothermal materials, and in particular to a high-flexibility and high-conductivity electrothermal film, a preparation method and application thereof in heating gloves. Background Art

[0002] With the rapid development of wearable electronic devices, the demand for the application of flexible electric heating elements in fields such as smart heating gloves is growing. As a heating unit that is in direct contact with the human body, the electric heating film not only needs to have excellent conductivity to ensure heating efficiency and temperature uniformity, but also has good flexibility to adapt to the repeated deformation caused by hand movement, and has self-healing function to extend the service life. The development of high-performance electric heating films is of great significance to improving the user experience of wearable heating devices and expanding the application scope of smart fabrics. Especially in outdoor sports, industrial production and other scenarios in cold environments, the comprehensive performance of electric heating films directly affects the practicality and reliability of the products. Therefore, the development of electric heating films with high flexibility, high conductivity and self-healing functions is of great practical significance to promote the advancement of smart wearable technology and meet market demand.

[0003] At present, the development of electric heating film materials still faces some technical bottlenecks, especially in the balance of flexibility, self-healing and conductivity. For example, Chinese patent CN113861594A discloses an electric heating film, but it has deficiencies in flexibility, self-healing and conductivity. On the one hand, although conductive polymers have certain flexibility, they are prone to mechanical fatigue under repeated bending or high stress environments, resulting in structural damage and performance degradation; on the other hand, the conductivity of conductive polymers is relatively low, and it is difficult to achieve an ideal heating effect at a lower voltage, and the resistance is prone to fluctuations over time and environmental changes, affecting the uniformity and efficiency of heating. In particular, there are obvious deficiencies in the dispersibility of conductive fillers, interfacial compatibility, and coordinated optimization of network structures, which makes it difficult for films to simultaneously meet the requirements of high flexibility, high conductivity and self-healing performance in practical applications. Therefore, it is urgent to develop new material systems and preparation processes to solve these technical problems. Summary of the invention

[0004] (1) Technical issues solved

[0005] The purpose of the present invention is to provide a highly flexible and highly conductive electric heating film, a preparation method and its application in heating gloves, so as to solve the problems of insufficient flexibility, conductivity and self-healing performance of the current electric heating film.

[0006] (2) Technical solution

[0007] In order to achieve the above object, the present invention provides the following technical solutions:

[0008] A highly flexible and highly conductive electric heating film is made of the following components by weight: 30 to 55 parts of a doped conductive prepolymer, 4.0 to 8.0 parts of a surface-modified graphene / carbon nanotube composite filler, 10 to 20 parts of a styrene-ethylene-butylene-styrene block copolymer, and 15 to 25 parts of N-methylpyrrolidone;

[0009] The doped conductive prepolymer is prepared from the following components by weight: 1.2 to 3.6 parts of poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid), 0.12 to 0.18 parts of lithium bis(trifluoromethanesulfonyl imide), 0.12 to 0.36 parts of cobalt phthalocyanine, 0.06 to 0.09 parts of ethylene glycol and 100 parts of deionized water;

[0010] The surface-modified graphene / carbon nanotube composite filler is obtained by surface-modifying the graphene / carbon nanotube composite filler with concentrated sulfuric acid and concentrated nitric acid;

[0011] The graphene / carbon nanotube composite filler is composed of carbon nanotubes and graphene uniformly distributed on the surface of the carbon nanotubes in an in-situ growth manner in a divergent manner.

[0012] The present invention adopts the design of doping poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) with lithium bis(trifluoromethanesulfonyl imide) and cobalt phthalocyanine, which is mainly used to enhance the flexibility and conductivity of thermoelectric films. The core design idea is to improve the comprehensive performance of poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) (PEDOT:PSS) film through a dual doping strategy, combined with the synergistic effect of each component, especially in terms of flexibility, conductivity and thermoelectric performance. First of all, poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) as the matrix material of the present invention has good conductivity and film-forming properties, and is widely used in the fields of electronic devices and flexible materials. However, pure PEDOT:PSS has certain limitations in the flexibility and conductivity of the film due to the strong interaction of its internal polymer segments. In order to overcome this problem, the present invention enhances the flexibility of the film by introducing lithium bis(trifluoromethanesulfonyl imide as a plasticizer. Lithium bis(trifluoromethanesulfonyl)imide can interact with polymer chain segments, destroying the original chain aggregation structure, thereby increasing the free volume of the film and improving the mobility of the molecular chain. This process allows the film to be stretched and deformed to a greater extent under the action of external forces, thereby significantly enhancing its mechanical flexibility. At the same time, lithium bis(trifluoromethanesulfonyl)imide can easily interact with negatively charged PSS - and positively charged PEDOT +The interaction between PSS and PEDOT chains is weakened, and the weakened Coulomb interaction between PSS and PEDOT chains decouples PEDOT from highly curled PSS and grows into large-scale conductive domains, forming a continuous nanofiber network, thereby improving the conductivity of the film. Secondly, cobalt phthalocyanine can interact with polymer chains to provide additional free holes, thereby increasing the effective carrier concentration in the film. This doping effect significantly improves the conductivity of PEDOT, allowing PEDOT:PSS films to achieve higher conductivity at lower doping concentrations. Lithium bis(trifluoromethanesulfonylimide) improves the flexibility of the film through plasticization and enhances the charge transport capacity of the film; while cobalt phthalocyanine increases the free hole concentration of the film through doping, further improving the conductivity and flexibility of PEDOT:PSS. The synergistic effect of the two not only optimizes the mechanical properties of the film, but also jointly improves the conductivity through different mechanisms, making the composite film have more outstanding performance in applications such as flexible electronic devices, thermoelectric energy conversion and electrochemical sensing.

[0013] As a key component in the electrothermal film, ethylene glycol plays multiple synergistic roles. First, ethylene glycol can induce PEDOT + and PSS - The rearrangement of the chains not only significantly improves the material's self-healing ability, but also enhances its electrical conductivity. Secondly, ethylene glycol improves the dispersion of surface-modified graphene and carbon nanotube composite fillers by adjusting the interfacial properties of the system, making the conductive network more uniform. This uniform dispersion further improves the flexibility of the film and ensures the stability and durability of the material in electrothermal applications.

[0014] The present invention enhances the flexibility and conductivity of thermoelectric thin films by designing surface-modified graphene / carbon nanotube composite fillers. The preparation of the composite filler includes two key steps: first, ferrocene and thiophene are used as catalysts and carbon sources, respectively, and graphene is grown in situ on the surface of carbon nanotubes by CVD method to achieve close combination of the two carbon nanomaterials; second, the composite filler is surface functionalized in a mixed solution of concentrated sulfuric acid and concentrated nitric acid to introduce oxygen-containing functional groups. The high conductivity of graphene and carbon nanotubes form a homogeneous interface, which is conducive to reducing electron scattering. Its long-range conductive channels are combined to form a multidimensional conductive network, and the structural characteristics of the two complement each other to provide excellent mechanical properties. Surface modification not only improves the compatibility of the filler with the matrix, but also enhances the dispersibility of the filler and avoids agglomeration. The design of this composite filler significantly improves the conductivity and mechanical properties of the thermoelectric film, and provides a new technical path for the development of high-performance thermoelectric materials.

[0015] Furthermore, the preparation method of the doped conductive prepolymer is as follows: by weight, 1.2 to 3.6 parts of poly (3, 4-ethylenedioxythiophene) -poly (styrene sulfonic acid), 0.12 to 0.18 parts of lithium bis (trifluoromethanesulfonyl imide), 0.12 to 0.36 parts of cobalt phthalocyanine, 0.06 to 0.09 parts of ethylene glycol and 100 parts of deionized water are mixed, and stirred at a speed of 1000 to 1500 rpm for 4 to 8 hours.

[0016] Furthermore, the mass ratio of lithium bis(trifluoromethanesulfonyl)imide, cobalt phthalocyanine, ethylene glycol and poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid) is 1:(1-2):0.5:(10-20).

[0017] Furthermore, the preparation method of the surface modified graphene / carbon nanotube composite filler is as follows: by weight, 20 to 45 parts of the graphene / carbon nanotube composite filler are added to 100 parts of a mixed solution of concentrated sulfuric acid and concentrated nitric acid, wherein the volume ratio of concentrated sulfuric acid to concentrated nitric acid is 3:1, and the concentrations of concentrated sulfuric acid and concentrated nitric acid are 98% and 70%, respectively; then ultrasonic stirring is performed for 60 to 90 minutes, and after filtering, the filter residue is repeatedly washed with deionized water until the pH value of the filtrate is 7; and finally, the surface modified graphene / carbon nanotube composite filler is obtained after vacuum drying.

[0018] Furthermore, the preparation method of the graphene / carbon nanotube composite filler is as follows: after uniformly mixing 0.2 to 0.5 parts of ferrocene, 2.0 to 10.0 parts of thiophene, 10 to 40 parts of carbon nanotubes and 100 parts of ethanol by weight, ultrasonically mixing for 30 to 45 minutes, filtering and vacuum drying the filter residue, placing it in a quartz tube, heating it to 1000 to 1200° C. in an argon gas flow of 200 to 300 sccm and keeping it warm for 90 to 120 minutes, and finally cooling it to room temperature to obtain the graphene / carbon nanotube composite filler.

[0019] Furthermore, the mass ratio of carbon nanotubes to graphene in the graphene / carbon nanotube composite filler is (60-85)%:(15-40)%.

[0020] Furthermore, the mass ratio of ferrocene, thiophene and carbon nanotubes is 1:(10-20):(50-80).

[0021] The present invention adopts a carefully designed material system, which is mainly used to enhance the flexibility and conductivity of thermoelectric films. By matching graphene and carbon nanotube composite fillers, a composite structure is formed with 60-85% carbon nanotubes and 15-40% graphene, and the two work together to effectively improve the conductive network of the film. The high aspect ratio of carbon nanotubes provides continuity for the conductive path, while the two-dimensional sheet structure of graphene enhances the coverage and stability of the conductive network, thereby maintaining good conductivity under different stress states. In addition, ferrocene is used as a catalyst, thiophene is used as a carbon source, and the preparation parameters of the filler are further optimized according to the mass ratio of 1: (10-20): (50-80) with carbon nanotubes. Under high temperature conditions, ferrocene catalyzes the decomposition of thiophene, promotes the growth of graphene sheets on the surface of carbon nanotubes, and forms a graphene / carbon nanotube composite structure with excellent conductive properties. The catalytic effect of ferrocene accelerates the growth process of graphene, while thiophene provides a carbon source, ensuring the efficient generation of graphene, and further improving the conductivity and thermal stability of the composite material. The synergistic improvement of material performance is achieved through the reasonable proportion design between the components. After the graphene and carbon nanotubes are compounded, the surface effect and interface interaction are enhanced, which further promotes the uniform dispersion of the filler in the matrix and avoids the aggregation of the material. This dispersion enhances the flexibility of the film, allowing it to maintain stable electrical properties during multiple bending and stretching processes. Through the design of this composite filler system, the present invention not only improves the conductivity of the thermoelectric film, but also gives it excellent mechanical flexibility, thereby meeting a wide range of application needs.

[0022] The present invention also provides a method for preparing a highly flexible and highly conductive electric heating film, comprising the following steps:

[0023] S1. Dispersing fillers: Add surface-modified graphene / carbon nanotube composite fillers and N-methylpyrrolidone into a mixing container according to the ratio, adjust the rotation speed to 1000-2000 rpm, and mix and stir for 30-45 minutes to obtain a dispersion.

[0024] S2. Prepare a mixed solution: add the doped conductive prepolymer and styrene-ethylene-butylene-styrene block copolymer to the dispersion obtained in S1 at the same time, heat to 60-80° C., adjust the stirring speed to 200-300 rpm, and stir for 30-45 min to obtain a mixed solution.

[0025] S3. Preparation of electric heating film: The mixed solution obtained in S2 is evenly coated on a glass substrate for curing at a curing temperature of 80 to 120°C and a heat preservation time of 30 to 60 minutes. After curing, it is vacuum dried at room temperature.

[0026] The invention also discloses the application of a high-flexibility and high-conductivity electric heating film, and the high-flexibility and high-conductivity electric heating film is used in heating gloves.

[0027] (3) Beneficial technical effects

[0028] 1. The modified PEDOT:PSS thermoelectric film prepared by the dual doping strategy of the present invention has significant application value and unique synergistic effect. Compared with the traditional single doping or modification method, the present invention adopts a dual doping system of lithium bis(trifluoromethanesulfonyl)imide and cobalt phthalocyanine, which effectively overcomes the problem of insufficient flexibility and conductivity of pure PEDOT:PSS film. Lithium bis(trifluoromethanesulfonyl)imide increases the free volume and improves the activity of the molecular chain by destroying the aggregation structure of the polymer chain, significantly enhancing the flexibility of the film; at the same time, its interaction with PSS and PEDOT promotes the formation of conductive domains and constructs a continuous nanofiber network. Cobalt phthalocyanine provides additional free holes through interaction with the polymer chain, increases the carrier concentration, and achieves high conductivity under low doping conditions. The synergistic effect of the two dopants not only optimizes the mechanical properties of the film, but also improves the conductivity through different mechanisms.

[0029] 2. The present invention realizes the in-situ growth of graphene on the surface of carbon nanotubes and strong acid surface modification by CVD method, which overcomes the problems of large interface contact resistance and poor dispersibility of traditional carbon nanomaterials. The structures of graphene and carbon nanotubes of homogeneous materials synergistically construct a multi-dimensional conductive network, and the surface functional groups enhance the interface bonding between the filler and the matrix, making the composite material have excellent application prospects in the fields of flexible electronics and thermoelectric conversion.

[0030] 3. Ethylene glycol as a key component induces PEDOT + and PSS - Chain rearrangement enhances the self-healing properties and electrical conductivity of the material, while improving the dispersion of graphene / carbon nanotube composite fillers, forming a uniform conductive network and improving the flexibility and stability of the film.

[0031] 4. The present invention achieves synergistic enhancement of the conductive network by optimizing the component ratio and preparation process of the graphene / carbon nanotube composite filler: carbon nanotubes provide a continuous conductive path, graphene enhances network coverage, and the catalytic system of ferrocene and thiophene promotes the formation of the composite structure. The uniform dispersion of the filler and the interfacial action improve the conductivity and flexibility of the film, allowing it to maintain stable performance when bent and deformed. Through a simple three-step preparation process, the film can be directly applied to flexible electric heating devices such as heating gloves. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a transmission electron microscope morphology image of the original carbon nanotubes used in Example 1 of the present invention.

[0033] Figure 2 This is a transmission electron microscope morphology image of the surface modified graphene / carbon nanotube composite filler prepared in Example 1 of the present invention.

[0034] Figure 3 This is the XRD spectrum of the surface-modified graphene / carbon nanotube composite filler prepared in Example 1 of the present invention.

[0035] Figure 4 This is the infrared Fourier spectrum of the surface-modified graphene / carbon nanotube composite filler prepared in Example 1 of the present invention.

[0036] Figure 5 This is a transmission electron microscope morphology image of the surface modified graphene / carbon nanotube prepared in Comparative Example 6 of the present invention. DETAILED DESCRIPTION

[0037] To make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.

[0038] In the case of not specifying specific conditions, the operation in the embodiment is carried out according to conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not indicated, are all common products on the market. The parts not mentioned in the technical content of the present invention will be processed with reference to the prior art. Unless otherwise specified, the following examples and comparative examples will be tested in parallel and use the same processing steps and parameters. Table 1 shows the reagents required for the examples and comparative examples and the corresponding purchasing companies.

[0039] Table 1 Reagents required for the examples and comparative examples and the corresponding purchasing companies

[0040]

[0041] Example 1

[0042] A highly flexible and highly conductive electric heating film is made of the following components by weight: 30 parts of doped conductive prepolymer, 4.0 parts of surface modified graphene / carbon nanotube composite filler, 10 parts of styrene-ethylene-butylene-styrene block copolymer, and 15 parts of N-methylpyrrolidone;

[0043] The heteroconductive prepolymer of this embodiment is made of the following components in parts by weight: 1.2 parts of poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid), 0.12 parts of lithium bis(trifluoromethanesulfonyl imide), 0.12 parts of cobalt phthalocyanine, 0.06 parts of ethylene glycol, and 100 parts of deionized water;

[0044] The surface-modified graphene / carbon nanotube composite filler of this embodiment is obtained by surface modification of the graphene / carbon nanotube composite filler by concentrated sulfuric acid and concentrated nitric acid; the graphene / carbon nanotube composite filler is composed of carbon nanotubes and graphene uniformly distributed on its surface in a divergent manner in an in-situ growth manner.

[0045] The preparation method of the doped conductive prepolymer of this embodiment is as follows: by weight, 1.2 parts of poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid), 0.12 parts of lithium bis(trifluoromethanesulfonyl imide), 0.12 parts of cobalt phthalocyanine, 0.06 parts of ethylene glycol and 100 parts of deionized water are mixed, and then stirred at a speed of 1000 rpm for 4 hours.

[0046] The preparation method of the surface-modified graphene / carbon nanotube composite filler of this embodiment is as follows: by weight, 20 parts of graphene / carbon nanotube composite filler are added to 100 parts of concentrated sulfuric acid and concentrated nitric acid mixed solution, wherein the volume ratio of concentrated sulfuric acid to concentrated nitric acid is 3:1, and the concentrations of concentrated sulfuric acid and concentrated nitric acid are 98% and 70% respectively, followed by ultrasonic stirring for 60 minutes, filtering and repeatedly washing the filter residue with deionized water until the pH value of the filtrate is 7, and finally vacuum drying to obtain the surface-modified graphene / carbon nanotube composite filler. The preparation method of the graphene / carbon nanotube composite filler is as follows: by weight, 0.2 parts of ferrocene, 2.0 parts of thiophene, 10 parts of carbon nanotubes and 100 parts of ethanol are mixed uniformly, first ultrasonically mixed for 30 minutes, then filtered and vacuum dried, and then placed in a quartz tube, heated to 1000°C in an argon gas flow of 200sccm for 90 minutes, and finally cooled to room temperature to obtain the graphene / carbon nanotube composite filler. The mass ratio of carbon nanotubes to graphene in the graphene / carbon nanotube composite filler is 60%:40%.

[0047] The method for preparing a highly flexible and highly conductive electric heating film of this embodiment comprises the following steps:

[0048] S1. Dispersing fillers: Add the surface-modified graphene / carbon nanotube composite filler and N-methylpyrrolidone into a mixing container according to the ratio, adjust the rotation speed to 1000 rpm, and mix and stir for 30 minutes to obtain a dispersion.

[0049] S2. Prepare a mixed solution: add the doped conductive prepolymer and the styrene-ethylene-butylene-styrene block copolymer to the dispersion obtained in S1 at the same time, heat to 60° C., adjust the stirring speed to 200 rpm, and stir for 30 min to obtain a mixed solution.

[0050] S3. Preparation of electric heating film: The mixed solution obtained in S2 is evenly coated on a glass substrate for curing at a curing temperature of 80°C and a heat preservation time of 30 minutes. After curing, it is vacuum dried at room temperature.

[0051] By analyzing the experimental results of the present invention, combined with Figures 1 to 5 The following conclusions can be drawn from the various characterization data: Figure 1The transmission electron microscope morphology image of the original carbon nanotubes used in Example 1 is shown, which clearly shows that the carbon nanotubes have a smooth surface and a hollow structure, indicating that their morphology is complete. Figure 2 The transmission electron microscope morphology of the surface-modified graphene / carbon nanotube composite filler prepared in Example 1 is revealed, proving that the graphene is evenly distributed on the surface of the carbon nanotube in a divergent manner, and this structure helps to enhance the construction of the conductive network. Figure 3 The XRD spectrum of the composite filler shows the effectiveness of the phase and further verifies the successful growth of graphene on carbon nanotubes. Figure 4 The infrared Fourier spectrum of the nanotubes further supports this conclusion. The peak at 1582 cm-1 corresponds to the C=C bond of the original carbon nanotubes, and the peak at 1160 cm-1 is the CC bond. After modification, the characteristic peaks of carbonyl and carboxyl groups appear at 1638 cm-1 and 1710 cm-1, respectively, indicating that these functional groups have been successfully introduced into the surface modification. Figure 5 The transmission electron microscope morphology in the graph proves that in comparative example 6, due to the lack of ferrocene catalysis, graphene cannot grow on the surface of carbon nanotubes, but instead forms nanocarbon balls, further verifying the key role of ferrocene in catalyzing the growth of graphene. In summary, the present invention achieves uniform growth of graphene on the surface of carbon nanotubes through ferrocene catalysis, and the surface modification process effectively introduces functional groups, significantly improving the performance of the composite material.

[0052] Example 2

[0053] A highly flexible and highly conductive electric heating film is made of the following components by weight: 38 parts of doped conductive prepolymer, 5.2 parts of surface modified graphene / carbon nanotube composite filler, 13 parts of styrene-ethylene-butylene-styrene block copolymer, and 18 parts of N-methylpyrrolidone;

[0054] The heteroconductive prepolymer of this embodiment is made of the following components in parts by weight: 1.9 parts of poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid), 0.14 parts of lithium bis(trifluoromethanesulfonyl imide), 0.19 parts of cobalt phthalocyanine, 0.07 parts of ethylene glycol, and 100 parts of deionized water;

[0055] The surface-modified graphene / carbon nanotube composite filler of this embodiment is obtained by surface modification of the graphene / carbon nanotube composite filler by concentrated sulfuric acid and concentrated nitric acid; the graphene / carbon nanotube composite filler is composed of carbon nanotubes and graphene uniformly distributed on its surface in a divergent manner in an in-situ growth manner.

[0056] The preparation method of the doped conductive prepolymer of this embodiment is as follows: by weight, 1.9 parts of poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid), 0.14 parts of lithium bis(trifluoromethanesulfonyl imide), 0.19 parts of cobalt phthalocyanine, 0.07 parts of ethylene glycol and 100 parts of deionized water are mixed, and then stirred at a speed of 1150 rpm for 5 hours.

[0057] The preparation method of the surface modified graphene / carbon nanotube composite filler of this embodiment is as follows: by weight, 28 parts of graphene / carbon nanotube composite filler are added to 100 parts of concentrated sulfuric acid and concentrated nitric acid mixed solution, wherein the volume ratio of concentrated sulfuric acid to concentrated nitric acid is 3:1, and the concentrations of concentrated sulfuric acid and concentrated nitric acid are 98% and 70% respectively, followed by ultrasonic stirring for 69 minutes, filtering and repeatedly washing the filter residue with deionized water until the pH value of the filtrate is 7, and finally vacuum drying to obtain the surface modified graphene / carbon nanotube composite filler. The preparation method of the graphene / carbon nanotube composite filler is as follows: by weight, 0.3 parts of ferrocene, 4.4 parts of thiophene, 19 parts of carbon nanotubes and 100 parts of ethanol are mixed uniformly, first ultrasonically mixed for 35 minutes, then filtered and vacuum dried, and then placed in a quartz tube, heated to 1060°C in an argon gas flow of 230sccm for 99 minutes, and finally cooled to room temperature to obtain the graphene / carbon nanotube composite filler. The mass ratio of carbon nanotubes to graphene in the graphene / carbon nanotube composite filler is 68%:32%.

[0058] The method for preparing a highly flexible and highly conductive electric heating film of this embodiment comprises the following steps:

[0059] S1. Dispersing fillers: Add the surface-modified graphene / carbon nanotube composite filler and N-methylpyrrolidone into a mixing container according to the ratio, adjust the rotation speed to 1300 rpm, and mix and stir for 35 minutes to obtain a dispersion.

[0060] S2. Prepare a mixed solution: add the doped conductive prepolymer and styrene-ethylene-butylene-styrene block copolymer to the dispersion obtained in S1 at the same time, heat to 66° C., adjust the stirring speed to 230 rpm, and stir for 35 min to obtain a mixed solution.

[0061] S3. Preparation of electric heating film: The mixed solution obtained in S2 is evenly coated on a glass substrate for curing at a curing temperature of 92°C and a heat preservation time of 39 minutes. After curing, it is vacuum dried at room temperature.

[0062] Example 3

[0063] A highly flexible and highly conductive electric heating film is made of the following components by weight: 45 parts of doped conductive prepolymer, 6.4 parts of surface modified graphene / carbon nanotube composite filler, 16 parts of styrene-ethylene-butylene-styrene block copolymer, and 21 parts of N-methylpyrrolidone;

[0064] The heteroconductive prepolymer of this embodiment is made of the following components in parts by weight: 2.6 parts of poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid), 0.16 parts of lithium bis(trifluoromethanesulfonyl imide), 0.26 parts of cobalt phthalocyanine, 0.08 parts of ethylene glycol, and 100 parts of deionized water;

[0065] The surface-modified graphene / carbon nanotube composite filler of this embodiment is obtained by surface modification of the graphene / carbon nanotube composite filler by concentrated sulfuric acid and concentrated nitric acid; the graphene / carbon nanotube composite filler is composed of carbon nanotubes and graphene uniformly distributed on its surface in a divergent manner in an in-situ growth manner.

[0066] The preparation method of the doped conductive prepolymer of this embodiment is as follows: by weight, 2.6 parts of poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid), 0.16 parts of lithium bis(trifluoromethanesulfonyl imide), 0.26 parts of cobalt phthalocyanine, 0.08 parts of ethylene glycol and 100 parts of deionized water are mixed, and then stirred at a speed of 1300 rpm for 6 hours.

[0067] The preparation method of the surface-modified graphene / carbon nanotube composite filler of this embodiment is as follows: by weight, 35 parts of graphene / carbon nanotube composite filler are added to 100 parts of concentrated sulfuric acid and concentrated nitric acid mixed solution, wherein the volume ratio of concentrated sulfuric acid to concentrated nitric acid is 3:1, and the concentrations of concentrated sulfuric acid and concentrated nitric acid are 98% and 70%, respectively, followed by ultrasonic stirring for 78 minutes, filtering and repeatedly washing the filter residue with deionized water until the pH value of the filtrate is 7, and finally vacuum drying to obtain the surface-modified graphene / carbon nanotube composite filler. The preparation method of the graphene / carbon nanotube composite filler is as follows: by weight, 0.4 parts of ferrocene, 6.8 parts of thiophene, 28 parts of carbon nanotubes and 100 parts of ethanol are mixed uniformly, first ultrasonically mixed for 39 minutes, then filtered and vacuum dried, and then placed in a quartz tube, heated to 1120°C in an argon gas flow of 260sccm for 108 minutes, and finally cooled to room temperature to obtain the graphene / carbon nanotube composite filler. The mass ratio of carbon nanotubes to graphene in the graphene / carbon nanotube composite filler is 75%:25%.

[0068] The method for preparing a highly flexible and highly conductive electric heating film of this embodiment comprises the following steps:

[0069] S1. Dispersing fillers: According to the ratio, the surface modified graphene / carbon nanotube composite filler and N-methylpyrrolidone are added into a mixing container, the rotation speed is adjusted to 1600 rpm, and the mixing and stirring time is 39 minutes to obtain a dispersion.

[0070] S2. Prepare a mixed solution: add the doped conductive prepolymer and styrene-ethylene-butylene-styrene block copolymer to the dispersion obtained in S1 at the same time, heat to 72° C., adjust the stirring speed to 260 rpm, and stir for 39 min to obtain a mixed solution.

[0071] S3. Preparation of electric heating film: The mixed solution obtained in S2 is evenly coated on a glass substrate for curing at a curing temperature of 104°C and a heat preservation time of 48 minutes. After curing, it is vacuum dried at room temperature.

[0072] Example 4

[0073] A highly flexible and highly conductive electric heating film is made of the following components by weight: 55 parts of a doped conductive prepolymer, 8.0 parts of a surface-modified graphene / carbon nanotube composite filler, 20 parts of a styrene-ethylene-butylene-styrene block copolymer, and 25 parts of N-methylpyrrolidone;

[0074] The heteroconductive prepolymer of this embodiment is made of the following components in parts by weight: 3.6 parts of poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid), 0.18 parts of lithium bis(trifluoromethanesulfonyl imide), 0.36 parts of cobalt phthalocyanine, 0.09 parts of ethylene glycol, and 100 parts of deionized water;

[0075] The surface-modified graphene / carbon nanotube composite filler of this embodiment is obtained by surface modification of the graphene / carbon nanotube composite filler by concentrated sulfuric acid and concentrated nitric acid; the graphene / carbon nanotube composite filler is composed of carbon nanotubes and graphene uniformly distributed on its surface in a divergent manner in an in-situ growth manner.

[0076] The preparation method of the doped conductive prepolymer of this embodiment is as follows: by weight, 3.6 parts of poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid), 0.18 parts of lithium bis(trifluoromethanesulfonyl imide), 0.36 parts of cobalt phthalocyanine, 0.09 parts of ethylene glycol and 100 parts of deionized water are mixed, and then stirred at a speed of 1500 rpm for 8 hours.

[0077] The preparation method of the surface-modified graphene / carbon nanotube composite filler of this embodiment is as follows: by weight, 45 parts of graphene / carbon nanotube composite filler are added to 100 parts of a mixed solution of concentrated sulfuric acid and concentrated nitric acid, wherein the volume ratio of concentrated sulfuric acid to concentrated nitric acid is 3:1, and the concentrations of concentrated sulfuric acid and concentrated nitric acid are 98% and 70%, respectively, followed by ultrasonic stirring for 90 minutes, filtering and repeatedly washing the filter residue with deionized water until the pH value of the filtrate is 7, and finally vacuum drying to obtain the surface-modified graphene / carbon nanotube composite filler. The preparation method of the graphene / carbon nanotube composite filler is as follows: by weight, 0.5 parts of ferrocene, 10.0 parts of thiophene, 40 parts of carbon nanotubes and 100 parts of ethanol are mixed uniformly, first ultrasonically mixed for 45 minutes, then filtered and vacuum dried, and then placed in a quartz tube, heated to 1200°C in a 300sccm argon gas flow for 120 minutes, and finally cooled to room temperature to obtain the graphene / carbon nanotube composite filler. The mass ratio of carbon nanotubes to graphene in the graphene / carbon nanotube composite filler is 85%:15%.

[0078] The method for preparing a highly flexible and highly conductive electric heating film of this embodiment comprises the following steps:

[0079] S1. Dispersing fillers: Add the surface-modified graphene / carbon nanotube composite filler and N-methylpyrrolidone into a mixing container according to the ratio, adjust the rotation speed to 2000 rpm, and mix and stir for 45 minutes to obtain a dispersion.

[0080] S2. Prepare a mixed solution: add the doped conductive prepolymer and the styrene-ethylene-butylene-styrene block copolymer to the dispersion obtained in S1 at the same time, heat to 80° C., adjust the stirring speed to 300 rpm, and stir for 45 min to obtain a mixed solution.

[0081] S3. Preparation of electric heating film: The mixed solution obtained in S2 is evenly coated on a glass substrate for curing at a curing temperature of 120°C and a heat preservation time of 60 minutes. After curing, it is vacuum dried at room temperature.

[0082] Comparative Example 1

[0083] The method is substantially the same as Example 1, except that lithium bis(trifluoromethanesulfonyl)imide is not added to the doped conductive prepolymer.

[0084] Comparative Example 2

[0085] The method is basically the same as Example 1, except that cobalt phthalocyanine is not added to the doped conductive prepolymer.

[0086] Comparative Example 3

[0087] It is basically the same as Example 1, except that ethylene glycol is not added to the doped conductive prepolymer.

[0088] Comparative Example 4

[0089] The method is basically the same as Example 1, except that the content of ethylene glycol in the doped conductive prepolymer is 0.1 parts.

[0090] Comparative Example 5

[0091] The method is substantially the same as Example 1, except that the content of lithium bistrifluoromethanesulfonyl imide in the doped conductive prepolymer is 0.15 parts.

[0092] Comparative Example 6

[0093] The method is basically the same as Example 1, except that ferrocene is not added in the preparation of the graphene / carbon nanotube composite filler.

[0094] Performance Testing:

[0095] Mechanical properties analysis: SANS-CMT4204 equipment was used to conduct tensile tests on the electric heating film samples, and the tensile rate was set to 2mm / min. The film to be tested was fixed on the test device according to the standard method, and the stress-strain data during the entire stretching process was recorded to obtain key parameters such as the tensile strength and maximum elongation of the sample to evaluate its mechanical performance characteristics.

[0096] Characterization of thermal and electrical conductivity: The conductivity and thermoelectric conversion characteristics of the samples were measured using the Japanese ADVANCE RIKO thermoelectric performance analyzer. The experiment was conducted in a constant temperature environment, and by applying a specific current and temperature gradient to the sample, its voltage response and temperature distribution change were measured. The conductivity and Seebeck coefficient of the sample were calculated based on the measured data to evaluate its performance indicators in the field of thermoelectric applications.

[0097] Evaluation of repair performance: A systematic study of the self-repairing properties of the film is conducted. First, the sample is precisely cut, and then the cut is tightly connected and fixed. The treated sample is placed in a humidity-controlled environment for 24 hours. The repaired sample is retested for mechanical properties and electrical conductivity, and its self-repairing effect is evaluated by comparing the changes in various indicators before and after repair. The test items include core parameters such as tensile properties, electrical conductivity, and thermoelectric properties.

[0098] The properties of the electric heating films of Examples 1 to 4 and Comparative Examples 1 to 6 are summarized in Table 2.

[0099] Table 2 Performance of the electrothermal films of Examples 1 to 4 and Comparative Examples 1 to 6

[0100]

[0101]

[0102] The main difference between Comparative Example 1 and Example 1 is that lithium bis(trifluoromethanesulfonyl imide) is not added. From the comparison results, it can be seen that the lack of lithium bis(trifluoromethanesulfonyl imide will cause the conductivity of the material to decrease significantly. This is because lithium bis(trifluoromethanesulfonyl imide) increases the free volume by destroying the aggregate structure of the polymer chain, improves the mobility of the molecular chain, and significantly enhances the flexibility of the film; at the same time, its interaction with PSS and PEDOT promotes the formation of conductive domains and constructs a continuous nanofiber network. At the same time, its absence will also affect the flexibility of the material, and the elongation will decrease.

[0103] The main difference between Comparative Example 2 and Example 1 is that cobalt phthalocyanine is not added. The experimental results show that the lack of cobalt phthalocyanine leads to a decrease in material performance, because cobalt phthalocyanine can provide additional free holes through interaction with polymer chains, increase carrier concentration, and achieve high conductivity under low doping conditions. Its absence directly affects the conductive properties of the material.

[0104] The main difference between Comparative Example 3 and Example 1 is that ethylene glycol is not added. The results show that the absence of ethylene glycol will significantly reduce the overall performance of the material, because ethylene glycol can induce PEDOT + and PSS - Chain rearrangement improves the self-healing performance and electrical conductivity of the material. At the same time, it can also improve the dispersion of graphene / carbon nanotube composite fillers, form a uniform conductive network, and improve the flexibility and stability of the film.

[0105] The main difference between Comparative Example 4 and Example 1 is that the ethylene glycol content is too high (0.1 parts). Experiments show that too high ethylene glycol content reduces the mechanical properties and electrical conductivity of the thermoelectric film.

[0106] The main difference between Comparative Example 5 and Example 1 is that the content of lithium bis(trifluoromethanesulfonyl)imide is too high (0.15 parts). The results show that excessive lithium bis(trifluoromethanesulfonyl)imide will destroy the balance of the material structure, affect the orderly formation of the conductive domain, and reduce the overall performance of the material.

[0107] The main difference between Comparative Example 6 and Example 1 is that ferrocene is not added. The results show that the lack of ferrocene affects the formation of graphene / carbon nanotube composite fillers, because ferrocene, as a catalyst, can form a catalytic system with thiophene to promote the formation of the composite structure. Its absence will affect the synergistic enhancement effect of the conductive network and reduce the material performance.

[0108] In summary, the modified PEDOT:PSS thermoelectric film prepared by the dual doping strategy and CVD method of the present invention combines the synergistic effect of lithium bis(trifluoromethanesulfonyl)imide and cobalt phthalocyanine, which effectively improves the flexibility and conductivity of the film. The in-situ growth of graphene on the surface of carbon nanotubes and the surface modification by strong acid construct a multidimensional conductive network, which overcomes the problems of large interface contact resistance and poor dispersion of traditional carbon nanomaterials. The introduction of ethylene glycol further optimizes the uniformity of the conductive network and the self-healing properties of the material. Through reasonable component ratios, optimized processes and uniform dispersion of fillers, the film of the present invention exhibits excellent performance in flexible electronics and thermoelectric conversion applications, and is particularly suitable for flexible electric heating devices such as heating gloves.

[0109] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that all equivalent structural changes made under the concept of the present invention and using the contents of the present invention specification and drawings should be covered within the scope of protection of the claims of the present invention.

Claims

1. A highly flexible and highly conductive electric heating film, characterized in that: The invention is prepared from the following components by weight: 30 to 55 parts of doped conductive prepolymer, 4.0 to 8.0 parts of surface modified graphene / carbon nanotube composite filler, 10 to 20 parts of styrene-ethylene-butylene-styrene block copolymer, and 15 to 25 parts of N-methylpyrrolidone; The doped conductive prepolymer is prepared from the following components by weight: 1.2 to 3.6 parts of poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid), 0.12 to 0.18 parts of lithium bis(trifluoromethanesulfonyl imide), 0.12 to 0.36 parts of cobalt phthalocyanine, 0.06 to 0.09 parts of ethylene glycol and 100 parts of deionized water; The surface-modified graphene / carbon nanotube composite filler is obtained by surface-modifying the graphene / carbon nanotube composite filler with concentrated sulfuric acid and concentrated nitric acid; The graphene / carbon nanotube composite filler is composed of carbon nanotubes and graphene uniformly distributed on the surface of the carbon nanotubes in an in-situ growth manner in a divergent manner.

2. A highly flexible and highly conductive electric heating film as claimed in claim 1, characterized in that: The preparation method of the doped conductive prepolymer is as follows: by weight, 1.2 to 3.6 parts of poly (3, 4-ethylenedioxythiophene) -poly (styrene sulfonic acid), 0.12 to 0.18 parts of lithium bis (trifluoromethanesulfonyl imide), 0.12 to 0.36 parts of cobalt phthalocyanine, 0.06 to 0.09 parts of ethylene glycol and 100 parts of deionized water are mixed, and then stirred at a rotation speed of 1000 to 1500 rpm for 4 to 8 hours.

3. A highly flexible and highly conductive electric heating film as claimed in claim 2, characterized in that: The mass ratio of lithium bis(trifluoromethanesulfonyl)imide, cobalt phthalocyanine, ethylene glycol and poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid) is 1:(1-2):0.5:(10-20).

4. The highly flexible and highly conductive electric heating film according to claim 1, characterized in that: The preparation method of the surface modified graphene / carbon nanotube composite filler is as follows: by weight, 20 to 45 parts of the graphene / carbon nanotube composite filler are added to 100 parts of a mixed solution of concentrated sulfuric acid and concentrated nitric acid, wherein the volume ratio of the concentrated sulfuric acid to the concentrated nitric acid is 3:1, and the concentrations of the concentrated sulfuric acid and the concentrated nitric acid are 98% and 70%, respectively; then ultrasonic stirring is performed for 60 to 90 minutes; after filtering, the filter residue is repeatedly washed with deionized water until the pH value of the filtrate is 7; and finally vacuum drying is performed to obtain the surface modified graphene / carbon nanotube composite filler.

5. A highly flexible and highly conductive electric heating film as claimed in claim 1 or 4, characterized in that: The preparation method of the graphene / carbon nanotube composite filler is as follows: after uniformly mixing 0.2-0.5 parts of ferrocene, 2.0-10.0 parts of thiophene, 10-40 parts of carbon nanotubes and 100 parts of ethanol by weight, ultrasonically mixing for 30-45 minutes, filtering and vacuum drying the filter residue, placing it in a quartz tube, heating it to 1000-1200° C. in an argon gas flow of 200-300 sccm and keeping it warm for 90-120 minutes, and finally cooling it to room temperature to obtain the graphene / carbon nanotube composite filler.

6. A highly flexible and highly conductive electric heating film as claimed in claim 1, 4 or 5, characterized in that: The mass ratio of carbon nanotubes to graphene in the graphene / carbon nanotube composite filler is (60-85)%:(15-40)%.

7. The highly flexible and highly conductive electric heating film according to claim 5, characterized in that: The mass ratio of ferrocene, thiophene and carbon nanotubes is 1: (10-20): (50-80).

8. A method for preparing a highly flexible and highly conductive electric heating film according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1. Dispersed filler: According to the ratio, the surface modified graphene / carbon nanotube composite filler and N-methylpyrrolidone are added to a mixing container, the speed is adjusted to 1000 to 2000 rpm, the mixing time is 30 to 45 min, and a dispersion is obtained; S2. Preparing a mixed solution: The doped conductive prepolymer and the styrene-ethylene-butylene-styrene block copolymer are simultaneously added to the dispersion obtained in S1, heated to 60 to 80 ° C, the stirring speed is adjusted to 200 to 300 rpm, the stirring time is 30 to 45 min, and a mixed solution is obtained; S3. Preparation of electric heating film: The mixed solution obtained in S2 is evenly coated on a glass substrate for curing at a curing temperature of 80 to 120°C and a heat preservation time of 30 to 60 minutes. After curing, it is vacuum dried at room temperature.

9. Use of a high-flexibility and high-conductivity electric heating film as described in any one of claims 1 to 8 or a high-flexibility and high-conductivity electric heating film prepared by the preparation method as described in claim 8 in electric heating gloves.

Citation Information

Patent Citations

  • Flame-retardant high-temperature-resistant PVC film for graphene electrothermal film and preparation method thereof

    CN113861594A

  • Combined graphene spheres and metal particles for anodes of alkali metal batteries

    CN114982010A

  • High-flexibility and high-conductivity electrothermal film for heating gloves and preparation method of high-flexibility and high-conductivity electrothermal film

    CN118459942A

  • Particulates of conducting polymer network-protected cathode active material particles for lithium batteries

    US20200350589A1

  • Electrode structures for lithium batteries

    US20220109142A1